DENSITY-GRADIENT PATTERNS OF STAPHYLOCOCCUS AUREUS CELLS AND CELL WALLS DURING GROWTH AND MECHANICAL DISRUPTION - Huff, Eskin (1964)
Huff, Eskin (National Institute of Allergy and Infectious Diseases, Bethesda, Md.), Harriet Oxley, and Carol S. Silverman. Density-gradient patterns of Staphylococcus aureus cells and cell walls during growth and mechanical disruption. J. Bacteriol. 88:1155–1162. 1964.—Procedures capable of rapid disruption of Staphylococcus aureus cells with optimal release of intact cell walls were investigated. This search was implemented by observation of the flotation patterns of cells and subcellular particulate matter after centrifugation in a cesium chloride density gradient. A quantitative evaluation of the light-scatter throughtout the gradient was achieved by transfer of the entire density gradient into an optical cell with wedge-shaped cross section. When this cell was photographed under indirect illumination, each band of light-scattering material appeared on the negative as a shaded curve, with an area proportional to amount of that material present. A series of photographs of known amounts of cells and cell walls was used to estimate the amounts of these materials in mixtures of the two occurring during mechanical disruption. With the methods employed, time studies established the optimal time for release of cell walls as 5 min in a Braun shaker. The use of sucrose gradients in the further purification of cell walls, and chemical analysis of the isolated walls, are described.